Dissolved organic nitrogen: A relevant, complementary source of nitrogen for the seagrass Zostera marina. (3rd April 2015) - Alexandre, Ana; Hill, Paul W.; Jones, Davey L.; Santos, Rui
Abstract: Dissolved organic nitrogen (DON) forms a significant pool of bioavailable N in the water column (62%) and in sediments of Ria Formosa lagoon (53%). We assessed the uptake rates of inorganic and organic nitrogen and its interactions in the seagrass Zostera marina, and further explored the possibility of seagrasses to use complex organic substrates (peptides). Uptake rates by leaves and roots were quantified in choice‐uptake experiments where plants were exposed to mixed N solutions containing both 15 N inorganic (ammonium + nitrate) and 13 C 15 N organic (alanine + trialanine) nitrogen at field‐relevant concentrations, and compared with uptake rates of single inorganic or organic N forms. Ammonia was the preferred N source, but plants preferred DON to nitrate. DON uptake was significantly higher through roots than leaves, coinciding with the one‐order of magnitude higher concentration of DON in the sediment than in the water. Not only amino acids, as reported elsewhere for other seagrasses, but also peptides constitute relevant N sources for Z. marina (10% and 4% of the total N uptake). Seagrasses may thus compete with microbes for organic substrates at an earlier stage of protein degradation in the N cycle than previously thought. Because no interactions occurred between inorganic and organic N sources, the total N uptake by Z. marina was higher when both sources were present, showing that organic nitrogen is a complementary rather than alternative source of nitrogen. The uptake of organic nitrogen should be included in future studies assessing the total N budgets of seagrass meadows.